Umbilical Cord Mesenchymal Stem Cells Secretome in Osteoarthritis Patients: A Case Report - Nurudhin, Arief; Prabowo, Nurhasan Agung; Wedhiningsih, Yulyani; Sunarso, Indrayana (Gema Lingkungan Kesehatan, 2025)
We report a case study of a 58-year-old lady diagnosed with symptomatic knee osteoarthritis (OA) who received umbilical cord-derived mesenchymal stem cell (UC-MSC) secretome via intra-articular injections once weekly for a total of five weeks. This treatment significantly reduced pain compared to the control, using a Visual Analog Scale, with pain scores reducing from 7/10 to 3/10. Moreover, the patient showed marked functional capacity improvement, as indicated by a Western Ontario and McMaster Universities Osteoarthritis Index score from 65 to 30. Her Kellgren-Lawrence grade also improved radiographically from 4 to 2 indicating either an initiation of cartilage regeneration or a reduction in degenerative change. These favorable results position the UC-MSC secretome as a novel and safe treatment for knee osteoarthritis, making it a potent non-invasive replacement therapy to classical treatments. The researchers advise that these findings must be confirmed in bigger, controlled trials before the therapeutic effects of UC-MSC secretome can be established in broader patient populations.